Ideological asymmetry in the relationship between epistemic motivation and political attitudes. [article]. - Federico, Christopher M.
Research on the psychological bases of political attitudes tends to dwell on the attitudes of conservatives, rarely placing conscious thematic emphasis on what motives liberals to adopt the attitudes they do. This research begins to address this imbalance by examining whether the need for cognitive closure is equally associated with conservatism in policy attitudes among those who broadly identify with the liberal and conservative labels. Counterintuitively, we predict and find that the need for closure is most strongly associated with policy conservatism among those who symbolically identify as liberals or for whom liberal considerations are made salient. In turn, we also find that the need for closure is associated with reduced ideological consistency in issue attitudes among liberal identifiers but not conservative identifiers. Although supportive of our predictions, these results run counter to a simple "rigidity of the right" hypothesis, which would predict a positive link between need for closure and policy conservatism regardless of ideological self-description and the "ideologue" hypothesis, which would predict a positive link between these variables among conservative identifiers and a negative one among liberal identifiers. We discuss the implications these findings for understanding the motivations underlying liberals, and conservatives' attitudes and suggest that future research attend to the important distinction between ideology in the sense of symbolic identification with conservatism versus liberalism and ideology in the sense of an average tilt to the right or left in one's policy attitudes. -(from the author)